PENGARUH PENDIDIKAN KESEHATAN TENTANG DIET DM TERHADAP PENINGKATAN PENGETAHUAN KELUARGA PENDERITA DM DI KELURAHAN BANYURADEN KECAMATAN GAMPING - Nurrohmad, Edi; Prabowo, Tri; Suwarno (Jurnal Media Ilmu Kesehatan, 2015)
Background: The number of people with diabetes mellitus in the world in 2030 is expected to 114%. Families can be a very influential factor in determining treatment program diabetes mellitus. Knowledge of diabetes mellitus family owned very necessary to improve the health status of the family, as a family should give good attention and care to the family members of people with diabetes mellitus. Objective: To determine the effectivity of health education about diabetes mellitus dietary to improving of knowledge in family with DM disease in the banyuraden district. Method: This research Design is Pre Experimental with pretest-posttest control group design. The Samples was choosen by purposive sampling technique, family with diabetes mellitus disease in Banyuraden, Gamping District of Sleman as much as 36 respondent. The research instrument was used questionnaire and it was analyzed by Independent Sample t-test. Results: level of knowledge family with diabetes mellitus disease about diabetes mellitus dietary on intervention and control group before given health education mayoritas is 55.6% less. After 7 days the level of knowledge intervention group became 66.7%, and control group is enough 72.2%. The results of independent sample t-test test between intervention and control group design shown that p-value = 0.000. Conclusion: There is an effectivity of health education about DM dietary to improving of knowledge in family with DM disease in the banyuraden district gamping. Keywords: Health education, diet diabetes mellitus, family knowledge